Research progress of nutrition support and nursing management of patients undergoing chemoradiotherapy for esophageal cancer (食管癌放化疗患者营养支持及护理进展) - PAN Chun (潘春); PANG Mi (庞咪); XU Yuanle (许远乐); SUN Fang (孙芳) (Association of Integrative Nursing, 2023)
Malnutrition is a common complication in patients undergoing chemoradiotherapy for esophageal cancer. This paper reviewed the studies on nutrition support and nursing management of patients undergoing chemoradiotherapy for esophageal cancer, and provided reference for clinical nursing practice. (营养不良是食管癌放化疗患者常见的并发症, 不仅影响整体治疗效果, 严重者可危及生命安全。本研究就食管癌放化疗患者营养支持及护理现状进行综述, 旨在为开展临床相关护理干预工作提供参考。)